A fractal accelerator on the basis of a corrugated plasma waveguide with superconducting walls - Tkachenko, I.V.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2019)
The use of a two-stage mechanism for the acceleration of charged particles is proposed. The principle of acceleration is based on the use of the fractal properties of the wave spectrum of a corrugated plasma waveguide with superconducting walls. The first stage provides for the excitation of a corrugated plasma waveguide by short electron bunches in the direction of motion (the length of the bunch is significantly less than the period of the corrugation). On the second stage the test charged particles accelerates in an infinite number of harmonics of the electric field exited by an electron bunches. Calculations show that with the implementation of such an acceleration mechanism, the average speed of a non-relativistic test particle can increase several times, and its acceleration length can be up to one meter. Запропоновано використання двоступеневого механізму прискорення заряджених частинок. Принцип прискорення заснований на використанні фрактальних властивостей хвильового спектра гофрованого плазмового хвилеводу з надпровідними стінками. Перший ступінь забезпечує збудження гофрованого плазмового хвилеводу короткими в напрямку руху електронними згустками (довжина згустку значно менше періоду гофра). Другий ступінь здійснює прискорення пробних заряджених частинок у збудженому електронними згустками нескінченному за кількістю гармонік електричному полі. Розрахунки показують, що при реалізації такого механізму прискорення середня швидкість нерелятивістської пробної частинки може збільшуватися в кілька разів, а довжина її прискорення може становити відстань до одного метра. Предложено использование двухступенчатого механизма ускорения заряженных частиц. Принцип ускорения основан на использовании фрактальных свойств волнового спектра гофрированного плазменного волновода со сверхпроводящими стенками. Первая ступень обеспечивает возбуждение гофрированного плазменного волновода короткими в направлении движения электронными сгустками (длина сгустка значительно меньше периода гофра). Вторая ступень осуществляет ускорение пробных заряженных частиц в возбужденном электронными сгустками бесконечном по количеству гармоник электрическом поле. Расчеты показывают, что при реализации такого механизма ускорения средняя скорость нерелятивистской пробной частицы может увеличиваться в несколько раз, а длина ее ускорения может составлять расстояние до одного метра.